Rapid molecular identification of freshly squeezed and reconstituted orange juice - Ng, C. C.; Chang, C. C.; Wu, I. C.; Kotwal, S.; Shyu, Y. T. (International Journal of Food Science and Technology, 2006)
This work presents a rapid and accurate molecular approach in the identification of freshly squeezed and reconstituted orange juice. Primers were designed based on the 18S and internal transcribed spacer (ITS) region. The findings indicated that self-made freshly squeezed orange juice heated to 80 degrees C for 30 s caused damage to DNA integrity, thus failing in amplification by primer 18S-ITSe, which gives a polymerase chain reaction product of 2081 bp, whereas primer 18S-ITSf, fragment length 2421 bp, could only be seen in heating conditions less stringent than 70 degrees C, 15 s. This new DNA integrity-dependent method has potential applications in identifying adulteration of freshly or processed orange juice.
Keywords: adulteration; citrus; DNA degradation; molecular detection; reconstituted juice